Seed germination of selected plants under the influence of heavy metals = Wpływ wybranych soli metali ciężkich na siłę kiełkowania nasion niektórych roślin - Drab, Michał; Greinert, Andrzej; Kostecki, Jakub; Grzechnik, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper has been presented the influence of selected heavy metals salts solutions: CuSO4, Pb(NO3)2, ZnCl2 and Cd(NO3)2 on the germination of seeds of the higher plants. The solutions with the various concentrations of abovementioned salts have been tested on seeds of the following plants: rye (Secale cereale L.), common wheat (Triticum aestivum L.), rape (Brassica napus oleifera L.) and white mustard (Sinapis alba L.).
Keywords: kadm; miedź; metale ciężkie; kiełkowanie; nasiona; cadmium; copper; germination; heavy metals; lead; seeds; zinc